Analysis of the Economics of Tobacco in Morocco - Omar Aloui (World Bank, Washington, DC, 2013)
This study of the tobacco industry and taxation policy in Morocco summarizes tobacco expenditure data from surveys, and looks at trends in these expenditures. The taxation and price policy implemented by the Moroccan government through the R?gie des Tabacs is described, and the overall contribution of the industry to tax revenues is estimated. The report briefly describes how the industry is organized, including farming activities, processing, marketing and the distribution network. Effective rates of taxation by categories of brands are estimated. The study then analyses the impact of price and taxation policy on tobacco demand and tax revenues. Data and estimation model specifications are described, and the results presented of different simulations of tax/price increases on tobacco consumption and tax revenues. The analysis shows that modest increases in tobacco tax rates in Morocco would generate additional revenues, and reduce consumption of tobacco products. Since few jobs are generated by the tobacco industry in Morocco, and 70 percent of all raw tobacco is imported, a fall in cigarette consumption would not be likely to cause any significant loss of employment. Moreover, as consumers switch their expenditures to other goods and services instead of cigarettes, the additional demand in other sectors of the economy will generate new jobs and incomes. The report concludes with recommendations for further research.